A ferroelectric polymer introduces addressability in electrophoretic display cells. (12th September 2019) - Sani, Negar; Mirbel, Déborah; Fabiano, Simone; Simon, Daniel; Engquist, Isak; Brochon, Cyril; Cloutet, Eric; Hadziioannou, Georges; Berggren, Magnus
Abstract: During the last decades, tremendous efforts have been carried out to develop flexible electronics for a vast array of applications. Among all different applications investigated in this area, flexible displays have gained significant attention, being a vital part of large-area devices, portable systems and electronic labels etc electrophoretic (EP) ink displays have outstanding properties such as a superior optical switch contrast and low power consumption, besides being compatible with flexible electronics. However, the EP ink technology requires an active matrix-addressing scheme to enable exclusive addressing of individual pixels. EP ink pixels cannot be incorporated in low cost and easily manufactured passive matrix circuits due to the lack of threshold voltage and nonlinearity, necessities to provide addressability. Here, we suggest a simple method to introduce nonlinearity and threshold voltage in EP ink display cells in order to make them passively addressable. Our method exploits the nonlinearity of an organic ferroelectric capacitor that introduces passive addressability in display cells. The organic ferroelectric material poly(vinylidene fluoride-co-trifluoroethylene) (P(VDF-TrFE)) is here chosen because of its simple manufacturing protocol and good polarizability. We demonstrate that a nonlinear EP cell with bistable states can be produced by depositing a P(VDF-TrFE) film on the bottom electrode of the display cell. The P(VDF-TrFE) capacitor and the EP ink cell are separately characterized in order to match the surface charge at their respective interfaces and to achieve and optimize bistable operation of display pixels.